Ibnu Rusyd: Warisan Intelektual, Pokok Ajaran Filsafat, dan Pengaruhnya dalam Khazanah Pemikiran Islam dan Barat - Suheri, Rofiqi Akrima (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
Ibn Rushd, or Averroes in the Western tradition, is one of the most influential figures in the history of Islamic and Western thought. The background to the emergence of Ibn Rushd's thought occurred during the golden age of Islamic civilization, when Greek philosophy was translated and re-examined in the context of Islam. In this atmosphere, Ibn Rushd emerged as a defender of rationality and efforts to harmonize revelation and reason. The purpose of this study is to examine Ibn Rushd’s intellectual legacy, formulate the main points of his philosophical teachings, and trace his influence on the treasures of Islamic and Western thought. This study uses a library research method with a historical-philosophical approach to examine Ibn Rushd's main works such as Tahafut al-Tahafut, Bidayat al-Mujtahid, and various commentaries on the works of Aristotle. The results of the study show that the main teachings of Ibn Rushd's philosophy are based on rational thinking and the defense of philosophy as part of the sharia, especially in interpreting religious texts using a common sense approach. He also emphasized the importance of logic as a tool for understanding reality. Ibn Rushd's influence is strongly felt in the tradition of rationalist Islamic thought, but more prominent in the West, especially in the scholastic and early Renaissance movements, through Latin thinkers such as Thomas Aquinas. The conclusion of this study states that Ibn Rushd is an important bridge between classical Islamic thought and modern Western philosophy, as well as a symbol of Islamic intellectualization that is open to dialogue between knowledge and faith.